TOM'S STORY BOOK - Murray, William; Corby, Jill Burton, Terry (Ladybird Books Ltd. London, 1993)
'Read With Me' adopts the look-say approach, introducing learners to the first 300 most frequently used words in the English language. Pronunciation and meaning are learned through gradual introduction and careful repitition